(untitled) (Third Sector Social Economic Review, 2025)
In this study, the short- and long-term interactions between the U.S. Standard & Poor’s 500 (S&P 500) stock market index and the UK FTSE 100 (FTSE) index were analyzed using daily data from January 3, 2005, to December 29, 2023. The analysis was conducted by employing the VAR model, Johansen cointegration test, Vector Error Correction Model (VECM) test, Granger causality test, and Wavelet coherence analysis techniques. The results of the Johansen cointegration test indicated that there is a long-term equilibrium relationship between the U.S. and UK stock indices; however, this relationship was not found to be strong. The VECM test reveals a strong short-term relationship between the two markets, showing that changes in the US stock index have an inverse effect on the UK stock market. The Granger causality test results indicate a causality relationship between the US and UK stock markets. The results of the Wavelet Coherence Analysis show that the long-term interaction between the US and UK stock markets is weak at periods of 32 and above, but there are strong fluctuations in the short term, particularly in the 2 to 8 period range. The study concludes that there is a strong short-term relationship and a weaker long-term relationship between the two stock markets. These findings suggest significant interaction between the US and UK stock markets, with interactions varying across time and frequency dimensions.